Analisa Posisi Peletakkan Baut terhadap Gaya Geser pada Sambungan Plat Baja - Sudjatmiko Sudjatmiko; I Made Sunada; Yanuar Wibisono (TRANSMISI, 2020)
Research on analysis the effect of positioning the use of bolts on the connection process between the two steel plates against the other steel plates to determine the magnitude of the bolt torque moment and the magnitude of the force. The connection of the steel plate components where the joints are used are able to with stand shear forces, pressure and torsion. The research objective was to determine the effective placement of the bolt position and the distance of the load on the vertical and horizontal bolt position to the magnitude of the torque due to compression  and the fracture model. Data collection was carried out in several tests of changes in the placement of the bolt joints, including the position of the bolts with three angles, in the vertical and horizontal position of the bolts.  The findings of the placement of the three-angle bolt position at 2-4-11 the shear force experienced a shift / fracture of the bolt greater than the shear force that occurred in the horizontal and vertical bolts position, with a pressure of 92.66 bar (torsion moment 108,342 kg-mm). Testing the position of the three-angle bolt at 2-6-10 where the vertical bolt was broken with a pressure of 65.33 bar ( torque  moment  76.401 kg-mm). The three-angle bolt placement test at 6-7-8 where the horizontal bolt was fractured at a pressure of 55.33 bar (torque  moment 64,701 kg- mm). Comparison of the placement of the bolts in the position of three angles of the shear force between the vertical and horizontal positions, the shear forces experience the greatest shift / fracture of the bolts in the vertical position. The loading distance affects the amount of shear force that occurs on the bolt. the farther the loading distance, the greater the shear force that occurs.